Integration of biomass gasification systems in a sugarethanol factory: Study of cases - Passolongo, Rodnei; Ramos, Ricardo Alan Verdú; Woiski, Emanuel Rocha; Maia, Cassio Roberto Macedo (My University, 2009)
This work presents a thermodynamic analysis of the integration of biomass gasification systems in a sugarethanol factory. It is considered the effect of gasification of the straw, bagasse and vinasse separately as well as the effect of their association by using additional equipments such as gasifier, gas turbine and heat recovery steam generator. The analysis is based on the application of the mass balance, first and second Thermodynamics Laws, considering a control volume for each plant equipment. Some parameters are defined to compare the products from different thermodynamic qualities such as thermal energy and power generation. The results show that there is a power gain in all cases including gasification, but bigger power generation and efficiencies are obtained when the bagasse gasification is involved, the highest with just bagasse. Although the vinasse gasification produces a gas with a higher Lower Heat Value, the additional energy produced is low in comparison with gasification of straw and bagasse technologies
Keywords: Bagasse; Gasification; Straw; Sugar-ethanol factory; Vinasse